The red-headed pilgrim : a novel - Maloney, Kevin (Fiction writer) (Two Dollar Radio, 2023)
"On a sunny day in a business park near Portland, Oregon, 42-year-old web developer Kevin Maloney is in the throes of an existential crisis that finds him shoeless in a field of Queen Anne's lace, reflecting on the tumultuous events that brought him to this moment. Growing up in the suburbs, young Kevin suffered "a psychological break that ripped me from my humdrum existence" mainlining high fructose corn syrup and episodes of The Golden Girls. Thus begins a journey of hard-earned insights and sexual awakening that takes Kevin from angst-ridden Beaverton to the beaches of San Diego, a frontier-themed roadside attraction in Helena, Montana, and a hermetic shack on an organic lettuce farm. Everything changes when Kevin falls in love with Wendy. After a chance tarot reading lands them on the frigid coast of Maine, their lives are unsettled by the birth of their daughter, Zoë, whose sudden presence is oftentimes terrifying, frequently disturbing, and yet--miraculously--always wondrous."--